2014
DOI: 10.1182/blood.v124.21.2245.2245
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 Is Overexpressed in B-Acute Lymphoblastic Leukemia (B-All) and Its Inhibition Sensitizes B-All Cells to Chemotherapeutic Drugs

Abstract: B-lymphoblastic leukaemic (B-ALL) patients that respond poorly to glucocorticoid therapy are predicted to relapse. An understanding of the biological mechanism underlying this poor responsiveness is therefore crucial for the development of more effective diagnostics and therapies. Forkhead box protein M1 (FOXM1) is a key transcriptional factor that regulates the expression of several genes that promote cell cycle progression, proliferation, DNA repair. Its expression is up-regulated in most cancer cells and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Multiple signaling pathways are associated with the FOXM1 signaling pathway, suggesting that FOXM1 is central to tumor aggressiveness (23). Previous studies have demonstrated that FoxM1 is upregulated in a wide variety of malignant tumors (23)(24)(25)(26). The current study demonstrated that FOXM1 is highly expressed in tissue samples of patients with CRC.…”
Section: Discussionsupporting
confidence: 52%
“…Multiple signaling pathways are associated with the FOXM1 signaling pathway, suggesting that FOXM1 is central to tumor aggressiveness (23). Previous studies have demonstrated that FoxM1 is upregulated in a wide variety of malignant tumors (23)(24)(25)(26). The current study demonstrated that FOXM1 is highly expressed in tissue samples of patients with CRC.…”
Section: Discussionsupporting
confidence: 52%
“…It has been reported that FOXM1 is a key downstream effector of the PI3K-AKT, ATM/p53-E2F, and p38-MAPK-MK2 signaling cascades (41,42,43), which also induces overexpression of both AURKA and AURKB, affecting chromosome alignment, mitotic spindle assembly, and bipolar spindle orientation further supporting the proposed pathway. FOXM1 may also act through PLK4 that was upregulated in our COPD cells and plays role in aberrant centrosome amplification inducing genomic instability.…”
Section: Discussionmentioning
confidence: 64%
“…To test whether Ara-C-resistant human and murine B-ALL cell lines have similar metabolic properties, we analyzed the ratio change of SoNar fluorescence in the Nalm6 cells, which have been used for drug resistance in a previous study (36). As shown in fig.…”
Section: Ara-c-resistant Human B-all Cell Line Has a Higher Level Of ...mentioning
confidence: 99%